A META-ANALYSIS: USE OF STUDENT WORKSHEETS BASED ON LOCAL WISDOM FROM 2013-2022 - Munjiatun Munjiatun; Otang Kurniaman; Guslinda Guslinda; Zufriady Zufriady; Siti Kurnia Rahayu; Yuyun Santika (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Research that was conducted by researchers from 2013-2022 has mostly been about teaching materials combined with local wisdom in learning in elementary and junior high schools (SMP). However, there is still certain research on students’ worksheets related to local wisdom based on the content of social science learning subjects in elementary schools. This article provides an overview of the percentage of use of student worksheets, the use of research methods, and the results or positive impacts or contributions of the research on the motivation of an educator to create or modify teaching materials based on local wisdom. Meta-analysis was carried out by searching for articles from web journals through Google Scholar and obtaining 50 articles that were saved in the research data documents. After the analysis, it was obtained that 30 articles matched the criteria. The meta-analysis that was carried out produced an overview that the most dominant percentage of students' worksheets was 27% in 2020 and the research method used was the R&D method with a percentage of 64%. And the results of the research were getting good responses from validators, teachers, and students with the average category being very good.